Effect of multi-frequency counter-current S type ultrasound pretreatment on the enzymatic hydrolysis of defatted corn germ protein: Kinetics and thermodynamics. (December 2019) - Musa, Abubakr; Ma, Haile; Gasmalla, Mohammed A.A.; Sarpong, Frederick; Awad, Faisal N.; Duan, Yuqing
Graphical abstract: Highlights: The ultrasound pretreatment enhanced the enzymatic hydrolysis of defatted corn germ protein. The enzymatic hydrolysis kinetics followed the First-order kinetic model. The ultrasound pretreatments of defatted corn germ protein reduced the thermodynamic parameters. Abstract: In this paper, the impact of ultrasound pretreatment on the kinetics and thermodynamics of defatted corn germ protein (DCGP) enzymatic hydrolysis was evaluated. The enzymatic hydrolysis kinetics and thermodynamics were studied for traditional method and ultrasonic pretreatments with a single-frequency counter-current S type (20 KHz) (SFU) and a multi-frequency counter-current S type (20, 28, 35 and 40 KHz) (MFU). The results showed that the traditional, SFU and MFU pretreated enzymatic hydrolysis of DCGP followed the First-order kinetic model. Again, the SFU and MFU pretreatments enhanced the enzymatic hydrolysis of DCGP. Compared to traditional enzymatic hydrolysis, the reaction rate constant values were increased by 50.0%, 54.7%, 47.8% and 52.3% for SFU pretreated enzymatic hydrolysis, and 58.0%, 58.5, 53.6% and 54.7% for MFU pretreated enzymatic hydrolysis at 20, 30, 40 and 50 º C respectively. Also, the results showed that the SFU and MFU ultrasound pretreatments of DCGP reduced the thermodynamic parameters which included the activation energy (Ea), enthalpy (ΔH), entropies (ΔS) and Gibbs free energy (ΔG) in enzymatic hydrolysis reaction.